CHRONOS: Compensating Hardware Related Overheads with Native Multi Timer Support for Real-Time Operating Systems

InTreeger: An End-to-End Framework for Integer-Only Decision Tree Inference

Resilient Endurance-Aware NVM-based PUF against Learning-based Attacks

WCDT: Systematic WCET Optimization for Decision Tree Implementations

Shielded reinforcement learning for fault-tolerant scheduling in real-time systems - Shi, Junjie; Chen, Kuan-Hsun (Real-Time Systems)
Abstract Reinforcement Learning (RL) has emerged as a promising tool for decision-making in various applications, particularly in uncertain environments. While its adoption in embedded systems—especially hard real-time systems—faces challenges due to stringent timing constraints, integrating shielding mechanisms may offer a pathway for RL to optimize its scheduling decisions, preserving worst-case timing guarantees. This position paper shows a use case where RL selects compliant execution versions for fault-tolerant real-time systems while minimizing the system utilization in runtime. Furthermore, we discuss possible directions for further exploring RL’s role in real-time systems for improved adaptability.

Introduction to the Special Issue on Fault-Resilient Cyber-Physical Systems—Part 2 - Chen, Kuan-Hsun; Li, Jing; Reghenzani, Federico; Chen, Jian-Jia (ACM Transactions on Cyber-Physical Systems)

Introduction to the Special Issue on Fault-Resilient Cyber-Physical Systems—Part 2 - Chen, Kuan-Hsun; Li, Jing; Reghenzani, Federico; Chen, Jian-Jia (ACM Transactions on Cyber-Physical Systems)

Wedge-Parallel Triangle Counting for GPUs - Spaan, Jeffrey; Chen, Kuan-Hsun; Bader, David A.; Varbanescu, Ana-Lucia (Lecture Notes in Computer Science)

Bloom Filters for Soft Error Detection: Neutron and Fault Injection Validation - Cishugi, Elijah Seth; Smit, Tijmen T.; Forlin, Bruno; Cazzaniga, Carlo; Chen, Kuan-Hsun; Ottavi, Marco (2025 IEEE 31st International Symposium on On-Line Testing and Robust System Design (IOLTS))

Optimizing Electric Vehicle Scheduling with Charging Guarantees using Flow Models with Local Penalties - Winschermann, Leoni; Günzel, Mario; Chen, Kuan-Hsun; Hurink, Johann (Proceedings of the 16th ACM International Conference on Future and Sustainable Energy Systems)

REAP-NVM: Resilient Endurance-Aware NVM-Based PUF Against Learning-Based Attacks - Nassar, Hassan; Wei, Ming-Liang; Yang, Chia-Lin; Henkel, Jörg; Chen, Kuan-Hsun (2025 Design, Automation & Test in Europe Conference (DATE))

LazyTick: Lazy and Efficient Management of Job Release in Real-Time Operating Systems - Heider, Kay; Hakert, Christian; Chen, Kuan-Hsun; Chen, Jian-Jia (ACM Transactions on Embedded Computing Systems)
Releasing jobs and performing scheduling decisions in real-time operating systems (RTOSes) is often realized within tick interrupts. In each tick interrupt, a set of tasks that are waiting to release new jobs, namely, the waiting set, is inspected to determine the jobs that should be released at this tick. Such a waiting set is sorted whenever a job has finished, by which the release process can be efficiently achieved. However, the overhead of sorting can vary vastly depending on the task set, which has to be taken into account in the worst-case timing analysis. Moreover, the tick interrupt in common practices is backed by a single hardware timer that is configured to trigger interrupts, either with a fixed period or reconfigured to the next release time (so-called one-shot timer). Since not necessarily at every interrupt a job will be released, several tick interrupts might be redundant. For the one-shot timers, the reconfiguration during runtime also incurs overheads at a variable interval. To reduce such variability and amount of overhead, in this work, we propose LazyTick which partitions the task set and distributes the subsets over multiple timers. Specifically, we propose two job release procedures with constant operations overhead—one for harmonic task sets and one for non-harmonic task sets. We implemented the support for multiple hardware timers in FreeRTOS and conducted intensive experimental evaluations. The evaluation shows that LazyTick can reduce the variability in overhead by up to ≈ 5 × in peak and ≈ 3× on average in comparison to the default implementation. Additionally, the combined overhead of the job release process is reduced by up to ≈ 6.1 × in peak and ≈ 3.6× on average.

Non-crossing partitions for exceptional hereditary curves - Baumeister, Barbara; Burban, Igor; Neaime, Georges; Schwabe, Charly Merlin (arXiv:2512.01729)
We introduce a new class of reflection groups associated with the canonical bilinear lattices of Lenzing, which we call reflection groups of canonical type. The main result of this work is a categorification of the corresponding poset of non-crossing partitions for any such group, realized via the poset of thick subcategories of the category of coherent sheaves on an exceptional hereditary curve generated by an exceptional sequence. A second principal result, essential for the categorification, is a proof of the transitivity of the Hurwitz action in these reflection groups.

TrackScorer: Skyrmion Logic-in-Memory Accelerator for Tree-Based Ranking Models - Cishugi, Elijah Seth; Buschjäger, Sebastian; Noorlander, Martijn; Ottavi, Marco; Chen, Kuan-Hsun (2025 Design, Automation & Test in Europe Conference (DATE))

Towards the tropicalization of reductive groups - Coles, Desmond; Ulirsch, Martin (arXiv:2503.21654)
Let $G$ be a connected reductive algebraic group over an algebraically closed field of characteristic zero carrying the trivial valuation. In this article we discuss two candidates for what could be the tropicalization of $G$. Our first suggestion is the extended affine building associated to $G$. This perspective makes makes use of Berkovich's embedding of the extended affine building into the Berkovich analytic space $G^{an}$ and expands on work of Mumford by associating a toroidal bordification of $G$ to the choice of stacky fan in the building. We show that the natural retraction onto the building is compatible with the tropicalization map associated to a toroidal bordification. Our second suggestion is a Weyl chamber of $G$, a special instance of spherical tropicalization, where we think of $G$ as a spherical $G× G$-variety with respect to left-right-multiplication. We show that the spherical tropicalization map may be identified with the toroidal tropicalization map associated to a wonderful compactification of $G$. This map also has a moduli-theoretic interpretation expanding on the compactifications of $G$ as moduli spaces of framed $\mathbb{G}_m$-equivariant principal bundles on chains of projective lines introduced by Martens and Thaddeus.

Tropical reductive groups and principal bundles on metric graphs - Gross, Andreas; Kuhrs, Arne; Ulirsch, Martin; Zakharov, Dmitry (arXiv:2511.05422)
We propose an elementary tropical analogue of a reductive group that combines the datum of a Weyl group and the tropicalization of a fixed maximal torus. For the classical groups, as well as $G_2$, these tropical reductive groups admit descriptions as tropical matrix groups that resemble their classical counterparts. Employing this perspective, we introduce tropical principal bundles on metric graphs and study their explicit presentations as pushforwards of line bundles along covers with symmetries and extra data. Our main result identifies the essential skeleton of the moduli space of semistable principal bundles on a Tate curve with its tropical analogue.

Statistics and data science education as a vehicle for empowering citizens – short summary of a survey - Biehler, Rolf; Kawakami, T.; Lampen, E.; Weiland, T.; Zapata-Cardona, L. (Proceedings of the 15th International Congress on Mathematical Education)

#Me Too in Science
Sexualisierte Diskriminierung und Gewalt galten in Hochschulen lange als Tabu und wurden vor allem durch Geschlechterforscher*innen und Gleichstellungsbeauftragte thematisiert. Mit der weltweiten #MeToo-Bewegung erhielt die Debatte um sexualisierte Diskriminierung und Gewalt in der Wissenschaft eine neue Dynamik. Der Band, der aus einer zweiteiligen Tagung an der Ruhr-Universität Bochum und der Universität Paderborn hervorgegangen ist, legt einen Schwerpunkt auf die historischen Dimensionen des Themenfeldes. Die Institution Hochschule und die Traditionslinien sowie die (Abwehr-)Diskurse zu sexualisierter Diskriminierung und Gewalt werden beleuchtet, die auch die gegenwärtigen Verhandlungen und (Nicht-)Bearbeitungen prägen. Der Band gibt Einblicke in die juristische Debatte und den gegenwärtigen Forschungsstand. Vorgestellt werden zudem Analysen und Präventionskampagnen aus der universitären Praxis, die auf unterschiedliche soziale Räume und die Spezifika verschiedener Fachkulturen eingehen.

Parental perceptions of inclusive teacher and school support – Establishment of a short-form - Knickenberg, Margarita; Kullmann, Harry; Wüthrich, Sergej; Sahli Lozano, Caroline

Die Standardberufsbildposition "Umweltschutz und Nachhaltigkeit" im Betrieb umsetzen - Jenninger, Isabell; Taskaya, Ayce (Ausbilder-Handbuch: Aufgaben, Konzepte, Praxisbeispiele)